RESEARCH OF MOTIVATION OF FUTURE ENGINEERS OF COMPUTER PROFESSIONAL PEDAGOGES - Yesipova, Olha (Educological discourse, 2019)
The article analyzes the scientific literature of domestic and foreign scientists, on the basis of which the approaches to the concept of motivation (motivation as a combination of factors and motives, motivation as a process and mechanism of activity, motivation as a set of all determinants of behavior) and a motive (an internal position of the student; driving force of the student). On the basis of the analysis of leading editions and own understanding of the concept of motivation, in the context of the scientific article, the concept of motivation will be understood as a set of factors and motives. The analysis of the educational activities of future engineers-teachers of the computer profile has shown that low motivation is one of the reasons for the lack of interest of those who are taught in the educational process while studying pedagogical disciplines. On the basis of the questionnaire on the methodology «The motivation of students studying at higher educational institution», the prevailing external and pragmatic motives for future engineers-teachers of the computer profile were established. In the course of student interviewing, it has been established that the regress of motives from the domestic ones in the process of entering the institution of higher education and the actual ones arose as a result of the fact that 61% of students disappointed in choosing their future profession. According to the results of interviews, the respondents found a low level of motivation in the process of studying humanitarian disciplines, including the pedagogical cycle. The survey shows that 64% of students do not see themselves as teachers, 73% study pedagogical disciplines because they are included in the curriculum and are mandatory. On the other hand, the information society creates demand for skilled workers in the IT industry, whose training can only be provided by highly skilled engineers-teachers of the computer profile provided that they have the appropriate pedagogical training. Recommendations on formation of positive motivation of students are developed.